Fiduciary principles in English common law - Getzler, J (Oxford University Press, 2019)
This chapter discusses fiduciary principles in the historical English common law. The term “fiduciary” today connotes high standards of loyalty and good faith in the performance of discrete obligations, the management of assets or the conduct of relationships, and the concept of fiduciary duty is often traced back to equitable notions of good conscience and undivided loyalty rooted in the moralistic approach of Chancery judges. However, a prior source of fiduciary standards lies in the common law doctrine of account. Legal accounting regulation began in the feudal age with Exchequer control of fees and services, rents and taxes. Feudal accounting was codified in the twelfth century to control the behavior of lords who stood as guardians for underage heirs, with particularly extensive duties being applied to guardians of wards in socage (or agricultural) tenure. Accounting systems were then extended to control management chains within manorial units embracing the lord’s farm agents of stewards, bailiffs, and reeves. The chapter then shows how the common law courts extended accounting and waste remedies to third parties through augmentation of disseisin actions to permit tracing and following procedures for entrusted assets. The prohibition of unauthorized profit-taking by fiduciaries or others in positions of influence or good faith and the use of an array of personal and proprietary remedies thus precedes the rise of the Court of Chancery by some three centuries. It is then shown how Chancery came to dominate fiduciary accounting procedures in modern times, building on an expansion of jurisdiction in the eighteenth century as the Chancellors struggled to repress managerial fraud in the private and public spheres. Today, following fusion of law and equity, we are seeing the assimilation of equitable remedies for breach of fiduciary duty with negligent liability for tortious harm, and the folding of the primary fiduciary duties into contract. Fiduciary accountability, born long ago within the early common law, is now being undermined by the blanket application of much simpler common law concepts.